The role of the deposit guarantee system in banking crises management: Case study of the Palestinian Deposit Insurance Corporation - Khelif, Abderrahmane; Medoukh, Madjeda (Journal of Human Sciences, 2022)
This study aims to shed light on the role of the deposit guarantee system as one of the most important financial safety nets, and is considered as a real guarantee for banks from the risks that they may be exposed to. Where this study reviewed the experience of the Palestinian Deposit Insurance Corporation in this regard and showed that there is a clear interest in the role of deposit insurance institutions in enhancing the effectiveness of the banking crisis management system in accordance with the best international standards and practices. The study also recommended the need to continue to strengthen and develop the deposit guarantee system and enhance the financial culture, as well as raising awareness of the role of the deposit guarantee system in crisis management.